Review about Ministry of Education: school ordination of the province of Castellón of 1950 - Santamaria Luna, Rogeli (Avances en Supervisión Educativa, 2017)
It is a review about the document recently published on the web and some comments. Author: Inspection of Primary Education of Castellón Current place of publication: http://www.mecd.gob.es/dms/mecd/servicios-al-ciudadano-mecd/archivo-central/exposiciones-virtuales/Arreglo-Escolar-Castellon/Arreglos/Arreglos.pdf Original production year: 1950 Pages: 274 Initial preparation format: paper Download format: pdf